Patterns in contrast - Ebeling, Jarle (Studies in corpus linguistics., 2013)
Atter og fram, det er lige langt; - ud og ind, det er lige trangt!?Forward and back, and it's just as far. Out and in, and it's just as strait.?Henrik Ibsen, Peer Gynt.